2022
DOI: 10.1002/cey2.252
|View full text |Cite
|
Sign up to set email alerts
|

Point‐to‐face contact heterojunctions: Interfacial design of 0D nanomaterials on 2D g‐C3N4 towards photocatalytic energy applications

Abstract: Green energy generation is an indispensable task to concurrently resolve fossil fuel depletion and environmental issues to align with the global goals of achieving carbon neutrality. Photocatalysis, a process that transforms solar energy into clean fuels through a photocatalyst, represents a felicitous direction toward sustainability. Eco-rich metal-free graphitic carbon nitride (g-C 3 N 4 ) is profiled as an attractive photocatalyst due to its fascinating properties, including excellent chemical and thermal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 442 publications
0
15
0
Order By: Relevance
“…With this exception, to obtain less expensive photocatalysts to pave the path for large-scale applications, metal-free semiconductors like g-C 3 N 4 have often been used in designing heterostructure photocatalysts owing to their enormous photocatalytic behavior. 179,180 This strategy was adopted in MXene-based photocatalysts as well, where Hu et al successfully constructed a 2D/2D Ti 3 C 2 /g-C 3 N 4 photocatalyst system via self-assembly electrostatic attractions. 181 Ti 3 C 2 NSs were adopted as electron collectors in this study, which not only aided charge transfer but also conceived an electron-rich environment on the surface of 2D Ti 3 C 2 , thereby endorsing the multi-electron CO 2 RR (Fig.…”
Section: Mxenes In the Catalytic Co2 Reduction Reactionmentioning
confidence: 99%
“…With this exception, to obtain less expensive photocatalysts to pave the path for large-scale applications, metal-free semiconductors like g-C 3 N 4 have often been used in designing heterostructure photocatalysts owing to their enormous photocatalytic behavior. 179,180 This strategy was adopted in MXene-based photocatalysts as well, where Hu et al successfully constructed a 2D/2D Ti 3 C 2 /g-C 3 N 4 photocatalyst system via self-assembly electrostatic attractions. 181 Ti 3 C 2 NSs were adopted as electron collectors in this study, which not only aided charge transfer but also conceived an electron-rich environment on the surface of 2D Ti 3 C 2 , thereby endorsing the multi-electron CO 2 RR (Fig.…”
Section: Mxenes In the Catalytic Co2 Reduction Reactionmentioning
confidence: 99%
“…Photocatalytic H 2 generation via water splitting which can convert abundant solar energy into clean hydrogen is considered one of the most prosperous ways to settle the urgent universal energy crisis and environmental problems. , Since the original research reported in 1972, there have been many studies surveying different kinds of semiconductor materials for the photocatalytic reaction. Among those semiconductors, CdS has been demonstrated to possess great potential for photocatalytic energy conversion owing to its relatively narrow band gap (∼2.4 eV of bulk phase) and strong reduction ability (high-conduct band position). However, bare bulk CdS suffers from a low photocatalytic performance because of its confined external active sites, fast recombination of photo-produced charge carriers resulting from long charge migration distance, and low light absorption ability. …”
Section: Introductionmentioning
confidence: 99%
“…[ 37–39 ] The 0D/2D point‐to‐face heterojunction exhibits a typical “point contact” interface, likely to result in severe charge congestions on the small interface region and extremely weak binding strength. [ 40,41 ] Coincidentally, in addition to the “point contact” interface, the 1D/2D line‐to‐face heterojunction mainly forms a “line contact” interface, which increases the electron transport path, but it is still challenging to achieve a larger contact area. [ 42 ] Due to the large size and variety of 3D materials, the 3D/2D bulk‐to‐face heterojunctions have complex contact interfaces.…”
Section: Introductionmentioning
confidence: 99%